Analisis Kadar Merkuri Dalam Rambut Penambang Emas Desa Alue Baro Kecamatan Meukek Secara Spektrofotometri Serapan Atom - M. Nasir*; Widya Rahmah; Ibnu Khaldun; M. Hasan; Rusman Rusman (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
The activity of using mercury in gold mining in Alue Baro Village, Meukek District is carried out freely so that it has a negative impact on the environment and the health of the miners. This study aims to determine the level of mercury in the hair of artisanal gold miners in Alue Baro village by referring to the reference that has been set by WHO. The data sample collection was carried out by taking 6 hair samples from the Alue Baro village gold miners who were selected with various types of work, namely gold processing, waste processing and waste waste until the time of the interview with a minimum working period of 1 year with sample codes R1, R2, R3, R4, R5 and R6 as control samples. The six samples were analyzed using Atomic Absorption Spectrophotometry equipped with a Mercury Analyzer which showed results, respectively, 1.01; 2.38; 1.65; 1.35; 1.66; and 0.64 ppm. The results of this study indicate that all hair samples have mercury levels above the mercury threshold that has been set by WHO, namely 1 ppm. High levels of mercury in hair samples were analyzed on exposure to mercury. Further research was conducted to analyze other metals contained in the hair of gold miners in Alue Baro village